PENGARUH ESG PERFORMANCE TERHADAP FINANCIAL DISTRESS RISK DENGAN PENGALAMAN LUAR NEGERI EKSEKUTIF SEBAGAI VARIABEL MODERASI - Abdillah Putra Dharmawan; Agung Juliarto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of ESG performance on financial distress risk, with executives’ foreign experience serving as a moderating variable. The study is motivated by the increasing importance of ESG implementation, particularly in the energy sector, which is characterized by high environmental exposure and financial risk, as well as the inconsistent findings of prior studies regarding the relationship between ESG and financial distress risk. In addition, empirical evidence on the moderating role of executive characteristics, especially foreign experience, remains limited. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. Using purposive sampling, a total of 38 observations were obtained and analyzed through Moderated Regression Analysis (MRA) with EViews 12. The results reveal that ESG performance has a significant negative effect on financial distress risk, indicating that companies with higher ESG performance tend to have a lower likelihood of experiencing financial distress. However, executives’ foreign experience is not proven to strengthen the negative effect of ESG performance on financial distress risk. Although the moderating effect is statistically significant, its direction is contrary to the proposed hypothesis, suggesting that executives’ foreign experience weakens the effectiveness of ESG performance in reducing financial distress risk. These findings highlight the importance of ESG as a mechanism for enhancing corporate financial resilience while indicating that international executive experience does not necessarily increase the effectiveness of ESG implementation in mitigating financial distress risk.